Aplikasi Pembelajaran Kuis Interaktif Ilmu Farmasi Berbasis Android - Aji Bagus; Ari Sulistiyawati; Lathifah Lathifah (Universitas Teknokrat Indonesia, 2023)
Based on the case studies that have been conducted, Ma'arif Kotagajah Vocational School majoring in Pharmacy only has 2 professional teaching staff. This causes an educational gap, due to a lack of teaching staff. Therefore, this study aims to produce a design and present an interactive quiz learning application as an additional learning application that can be useful for teachers and students. The method used in this research is the ADDIE development method, which consists of 5 stages namely Analysis, Design, Development, Implementation, and Evaluation. This study also tested the application using the ISO 25010 software testing standard, which has characteristics such as functional suitability, performance efficiency, usability and compatibility. Based on the results of the study, obtaining a feasibility percentage of 77.08% and belonging to the Eligible category. In the usability test, a feasibility presentation of 160% was produced and classified in the Very Eligible category. Compatibility testing on 4 different smartphone devices showed successful results. While testing performance efficiency, it only takes up 11.6 MB of memory.